Rural-urban disparities in educational well-being: a study of secondary school children in Sri Lanka - Careemdeen, Jalal Deen; Mohd Mahzan Awang (Penerbit Universiti Kebangsaan Malaysia, 2025)
This research paper explores the disparities in educational well-being among secondary school children in Sri Lanka based on geographic location, focusing on the differences between urban and rural contexts. Significant variation in resource allocation, school infrastructure, and parental educational backgrounds mark Sri Lanka's educational landscape, creating a diverse backdrop for the study. The research examines how these urban-rural disparities influence key dimensions of students' educational well-being, particularly access to educational resources and the development of hard, soft, and social skills that contribute to their ability to lead fulfilling and productive lives. The study aims to identify patterns of inequality, challenges, and opportunities that can inform policy-making and targeted interventions by focusing on the environments in which students live and learn. The research adopts a survey-based quantitative methodology, collecting data from a representative sample of 1,350 secondary school students across Sri Lanka. The data were analysed using Likert scales to measure educational well-being and a One-Way MANOVA to assess location-based differences. The findings indicate statistically significant differences in educational well-being across locations, with urban students scoring higher in all dimensions: access to resources, soft skills, social skills, and vocational skills. This study recommends targeted resource allocation, enhanced teacher training, skill development programmess, and comprehensive support systems, alongside further research, to improve educational well-being and ensure equitable opportunities for both urban and rural students.